ANALISIS BASIS EKONOMI DALAM MENINGKATKAN PERTUMBUHAN WILAYAH (STUDI PADA SEKTOR EKONOMI KOTA SURABAYA TAHUN 2016-2021) - Prayitno, Andaru Rachmaning Dias (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2023)
Increasing economic growth for each region is one of the main economic objectives to be achieved and is a benchmark for economic development. In realizing the regional economic development plan, the government has put it into the Indonesian national development plan system as well as regional economic development plans. The intention of writing a journal article is to examine and analyzing the basic sectors driving economic growth in the Surabaya metropolitan area and to analyze the structural pattern of economic growth in the development of urban areas. The kind of research use is descriptive quantitative with techniques that use Location Quotient (LQ) and typology class analysis. From the yield of the analyzing, it is known that the basic economic sector in the city of Surabaya in 2016-2017 is the multiplication of electricity and gas; water supply and waste management; building; wholesale and retail; Transportation and storage; Provide food and drink; communications information; financial services; vital space; financial services and health services. Meanwhile, Quadrant 1 of the Surabaya City Economic Structure Model 2016-2017 includes construction sector, the transportation and storage sector, the food and beverage sector, real estate sector, the business service sector, and the health sector. Quadrant 2 is the multiplication of the electricity and gas sector, the multiplication of the water and waste sector, wholesale and retail trade, information and communication, financial services and other services. Quadrant 3 is the industrial sector, the public sector and the educational sector. Quadrant 4 includes agriculture, forestry, fishing, and mining.